2015
DOI: 10.14814/phy2.12427
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of soluble epoxide hydrolase increases coronary perfusion in mice

Abstract: Roles of soluble epoxide hydrolase (sEH), the enzyme responsible for hydrolysis of epoxyeicosatrienoic acids (EETs) to their diols (DHETs), in the coronary circulation and cardiac function remain unknown. We tested the hypothesis that compromising EET hydrolysis/degradation, via sEH deficiency, lowers the coronary resistance to promote cardiac perfusion and function. Hearts were isolated from wild type (WT), sEH knockout (KO) mice and WT mice chronically treated with t-TUCB (sEH inhibitor), and perfused with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 46 publications
(103 reference statements)
2
20
0
Order By: Relevance
“…This finding implies that the female sex may possess a specific regulatory mechanism that mimics the Ephx2 gene deletion. Also, an unchanged 5,6-EET/DHET in response to disruption of the Ephx2 gene indicates that this isoform of EET is a poor substrate for sEH (36,46). Importantly, administration of 14,15-EET dose dependently elicited comparable increases in RVSP in all groups of mice (Fig.…”
Section: Changes In Rvspmentioning
confidence: 82%
See 1 more Smart Citation
“…This finding implies that the female sex may possess a specific regulatory mechanism that mimics the Ephx2 gene deletion. Also, an unchanged 5,6-EET/DHET in response to disruption of the Ephx2 gene indicates that this isoform of EET is a poor substrate for sEH (36,46). Importantly, administration of 14,15-EET dose dependently elicited comparable increases in RVSP in all groups of mice (Fig.…”
Section: Changes In Rvspmentioning
confidence: 82%
“…As described in detail (36,40), esterified EETs and DHETs from tissue extracts were quantified via LC/MS/MS (AB ScieX, Qtrap 3200). Protein concentration of samples, determined by the Bradford method (Bio-Rad, Hercules, CA), was used to normalize the detected lipids, such that each regioisomer of EETs and DHETs was expressed as picograms per microgram protein.…”
Section: Lc/ms/ms-based Measurements For Lung Eets and Dhetsmentioning
confidence: 99%
“…In the coronary circulation, coronary arteries are specifically exposed to a rhythmic compression generated by myocardial contraction. To this end, the pressure-sensitive mechanism becomes critically important in the regulation of coronary resistance and cardiac flow/perfusion (23,26,30,31,37). Although this pressuresensitive behavior originates from the smooth muscle layer of blood vessels that depolarizes in response to increases in pressure, and is therefore named as "myogenic response," the endothelial cells constitutively produce a variety of vasodilators such as endothelial nitric oxide (NO) that counteracts the pressure-induced vasoconstriction.…”
mentioning
confidence: 99%
“…These sums provide an index of the overall CYP450-mediated epoxygenation toward each of the fatty acids ( 6,16 ). We also secondarily assessed each MEFA regioisomer derived from the same PUFA, as well as the epoxide:diol ratio for each MEFA, an index that is inversely correlated with soluble epoxide hydrolase activity and has been suggested to be a proxy for the enzyme activity in vivo ( 17,18 ). We evaluated this ratio in our study because n-3 PUFA supplementation has been shown in animal studies to change soluble epoxide hydrolase expression ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme is therefore a potential therapeutic target, and the manipulation of its expression or activity (and therefore the epoxide:diol ratio) in animal studies infl uences infl ammation and other physiological parameters (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%